Pemanfaatan Limbah Fly-Ash Untuk Campuran Bata di Desa Umbul Limus Kecamatan Marga Punduh Kabupaten Pesawaran - Rajiman, Rajiman (Bhumiputra: Jurnal Penelitian dan Pengabdian Masyarakat Global, 2024)
This community service program aims to utilize fly ash waste as a mixture in brick production in Umbul Lumus Village, Marga Punduh District, Pesawaran Regency. The program was implemented using a community-based approach, involving the local community actively in every stage of the activity, from problem identification to production implementation. The results show that the community successfully produced high-quality fly ash-based bricks with higher compressive strength, lower water absorption, and better production cost efficiency compared to conventional bricks. In addition, this program also enhanced the community’s knowledge and skills in waste utilization and environmental management. Significant social impacts were observed, including increased environmental awareness, behavioral changes, and the formation of small business groups focused on fly ash-based brick production. This program is expected to serve as a model for sustainable community empowerment that can be applied in other areas to address waste issues and improve local economies.